Factors Associated with Mortality of COVID-19 in Elderly Diabetes Patients - บำรุงเสนา, กู้ศักดิ์ (Journal of Health Science of Thailand, 2023)
Older people with diabetes have a higher rate of death from COVID-19 than the general population. The purpose of this study was to determine the proportion of signs, symptoms, treatment outcomes and factors associated with COVID-19 mortality among elderly patients with diabetes. It was conducted as a retrospective cohort study of 175 diabetes elderly patients infected with COVID-19 who were admitted to Songkhla Hospital between May 2021 and May 2022. The data were collected from inpatient medical records. The hazard ratio was tested with multivariate cox proportional hazard regression. It was found that 73 of the 175 patients died (41.7%), with median age of 71.0 years, 40.0% were males, 45.1% had never been vaccinated against COVID-19, and 81.1% had co-morbid hypertension. The symptoms were cough, dyspnea and fever, 53.1%, 46.9% and 45.7%, respectively. Factors associated with COVID-19 mortality were age (HR=1.08, 95%CI=1.05–1.12), never vaccinated against COVID-19 (HR=1.88, 95%CI=1.13–3.14), cancer history (HR=3.58, 95%CI=1.35–9.49), respiratory rate (HR=1.13, 95%CI=1.08–1.19), protein albumin (HR=0.33, 95%CI=0.20–0.54), and aspartate transaminase (AST) (HR=1.01, 95%CI=1.00–1.01). Thus, the elderly with diabetes when infected with COVID-19 without having been vaccinated against COVID-19, had a history of cancer, fast breathing, low albumin protein or high AST are high risk of death. They should be closely monitored and treated as appropriate.